Animasi 3D Menggunakan Augmented Reality Sebagai Media Pengenalan Warisan Budaya Provinsi Riau - Dewi, Meilany; Liana Putri, Vania Ozva (Jurnal Komputer Terapan, 2024)
The city of Riau Province is a historic city that has cultural heritage in the form of old buildings. Tangible culture can be called Malay Intangible Heritage, which is still found today even though it has undergone development from the original, in the form of Gurindam 12, Malay clothes, Malay specialties, customs. Whereas currently tangible heritage such as Malay villages, traditional Malay houses, mosques, surau and others that are full of history and these values have almost disappeared due to modernization and globalization. So because of these problems, another alternative is needed to introduce the cultural heritage of Riau Province. In this study, an augmented reality application was built as a medium to recognize the cultural heritage of Riau Province. The method used is SDLC waterfall where the development is carried out systematically and sequentially. The results of system testing using Black box and Questionnaire show that the functionality is running well. In addition, the results of Content Validity testing on experts obtained an overall score of 95% which indicates that the application is very good. In addition, the pre test and post test also obtained the results of a large difference before and after using the application and it was proven that responders who had used the application became more knowledgeable about the cultural heritage of Riau Province.